Development of thin film structures for heterojunction bipolar transistors (HBTs) - Radhakrishnan, K. (2008)
In this study, MBE growth optimization for producing excellent device quality heterostructures has been reported, starting from single GaAs epi-layer. Based on this experience, several high electron mobility transistor devices have been fabricated and characterized.